The effect of a proposed (physical-skills) training-curriculum to develop the direct shooting skill of Wheelchair basketball players - Mohammed-J-Mnadi (Global Scientific Publishing, 2024)
The importance of the research was highlighted by the fact that the cases of disability are many and different according to the activities and games that individuals practice, including what is done using wheelchairs, which prompted the researcher to pay attention to this aspect and how to use wheelchairs in the game of basketball for the disabled, as it is one of the important games that is included in world championships. As for the problem of the research, it emerged through the researcher’s observation that there was a weakness in the performance of the direct shooting skill in basketball, and the reason may be physical or skillful, which prompted the researcher to study this case to develop the level of shooting skill performance for the players of the Thi Qar Committee in basketball for the disabled. Then the researcher touched on the most important There are two objectives for the research and the most important hypotheses of the researcher.
Keywords: important; hypotheses; researcher